Climate change, food security and economic growth nexus in the Gambia: Evidence from an econometrics analysis - Ebrima K. Ceesay; Mohamed Ben Omar Ndiaye (Research in Globalization, 2022)
This paper aims to test econometrically to analysis climate change on food security and other which includes economic growth, population growth and agriculture sector. This paper employed data for the period 1971-2020 from open data bank from (WDI) World development indicator and analyzed this data using Vector Autoregressive Approach (VAR), Granger Causality Approach, Autoregressive Distributed lag mode approach (ARDL) and Error Correction Approach (ECM). Empirical evidence displays, food security growth has strong optimistic correlation with the agriculture sector but negative correlation with rainfall variation. Finally, Population growth has significant negative impact on food security in a short term and insignificant negative impact on food security in the long term. Policy recommendation is that since agriculture is important for food security in the rural Gambia. The government should work on planting more trees for better agriculture and environment, Food security intervention programs, and Poverty reduction programs, provision of more adaptive capacity indicators, Quality and affordable education for all, System changes to bring quality of governance and institution and economic that is working for all and sundry, and consider export economy, the author noted.
Keywords: 330; ARDL technique; Economic growth; Food security; The Gambia; Variation in Rainfall